(untitled) (Asian Journal of Pharmaceutics (AJP), 2023)
A number of plant species belonging to the Syzygium genus are found all over the world. The majority of these plants exhibit a variety of biological activities, some of which have been documented and others which have not. Researcher interest therefore exists in the Syzygium genus. In an effort to discover new uses for them or a better dose at which they can be employed, all Syzygium species are being intensively researched. The diverse Syzygium species, their phytochemical components, and their pharmacological properties are the main topics of this review. Syzygium aromaticum, also known as clove; Syzygium samarangense, also known as Java apple; Syzygium anisatum; Syzygium caryophyllatum, also known as lilly pilly; Syzygium aqueum, also known as water apple; Syzygium jambos, also known as mountain apple; Syzygium cumini, also known as Java plum; and Syzygium australe were discussed in this review paper. Plants of the Syzygium species have been reported to have biological properties such as anti-diabetic, antioxidant, anti-bacterial, antiinflammatory, platelet inhibition, and hepatoprotective. All of the anti-diabetic properties are specifically mentioned in our current review. We made an effort to compile information as best as we could and hope that anyone studying or researching Syzygium will find it helpful. In this review article, S. cumini is given emphasis since it has a variety of applications and most of the plant’s parts have their own usage in the medical industry.